Left-Sided Implantation of a Defibrillator Lead in Persistent Left Superior Vena Cava - De Roo, Evelien (Eur J Case Rep Intern Med, 2020)
Persistent left superior vena cava (PLSVC) is a congenital venous abnormality, characterized by an enlarged coronary sinus, in most cases without haemodynamic consequences. We report the case of a patient with systolic heart failure undergoing implantation of a defibrillator lead through a PLSVC which was diagnosed at the moment of implantation. LEARNING POINTS: Persistent left superior vena cava (PLSVC) can be incidentally diagnosed during a procedure such as a left-sided central venous line or pacemaker implantation, and can be confirmed by manual contrast injection during the procedure. An enlarged coronary sinus on echocardiography should raise suspicion of PLSVC which can be confirmed by administration of echo-contrast or agitated saline in the left arm. Although lead implantation through a PLSVC is technically feasible, difficulties in lead positioning may be encountered because of the acute angle between the origin of the coronary sinus and the tricuspid valve.